The Level of Independence Among Seniors with a History of Ischemic Stroke - Izabela Wróblewska; Małgorzata Dziechciaż; Zuzanna Wróblewska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Stroke is currently among the most dangerous civilization diseases and the most common cause of death and secondary disability in people over 65 years of age. Disease-related disability significantly affects all spheres of human functioning, leading to dependence on third parties’ assistance. One of the most important activities to be undertaken in relation to a disabled patient is diagnosing the level of disability and implementing active efforts for the patient to regain optimal performance and/or accept the disability. Limitation in daily activities is a considerable stress factor that has a negative effect on the seniors’ recovery and becomes a cause of institutionalization. Aim. To investigate the impact of ischemic stroke on the level of independence in elderly people. Material and Methods. Medical records of 186 patients of a neurological ward were analysed. The majority of participants were women (55.91%), seniors aged 76–85 (36.02%), living in a city (55.38%) and being widowed (41.93%). The standardized Norton and Tinetti scales were applied in the analyses. Results. The most important factors influencing the incidence and course of stroke were the patient’s age and the presence of concomitant diseases: diabetes (81.72%) and arterial hypertension (73.65%). Among the stroke complications, the majority of patients presented aphasia (76.88%), hemiparesis (67.20%), dysphagia (63.44%) and urinary bladder dysfunction (60.21%). The study subjects were predominantly (86.56%) classified in the third category of care; 38.17% were referred for further rehabilitation in a post-hospital rehabilitation unit, 19.89% were referred to a medical care and treatment institution, and 19.36% died. The majority of the respondents achieved less than 14 points (77.96%) in the Norton scale and less than 19 points (34.41%) in the Tinetti scale. Conclusions. Ischemic stroke reduces or completely terminates the patient’s ability to function independently. The patient’s age is of greatest significance for the level of his independence and functioning immediately after ischemic stroke. (JNNN 2019;8(3):112–118)